Community Calls: Lessons and Insights Gained from a Medical–Religious Community Engagement During the COVID-19 Pandemic - Galiatsatos, Panagis (Journal of religion and health, 2020)
During the pandemic caused by the severe acute respiratory syndrome coronavirus-2, public health instructions were issued with the hope of curbing the virus’ spread. In an effort to assure accordance with these instructions, equitable strategies for at-risk and vulnerable populations and communities are warranted. One such strategy was our community conference calls, implemented to disseminate information on the pandemic and allow community leaders to discuss struggles and successes. Over the first 6 weeks, we held 12 calls, averaging 125 (standard deviation 41) participants. Participants were primarily from congregations and faith-based organizations that had an established relationship with the hospital, but also included school leaders, elected officials, and representatives of housing associations. Issues discussed included reasons for quarantining, mental health, social isolation, health disparities, and ethical concerns regarding hospital resources. Concerns identified by the community leaders as barriers to effective quarantining and adherence to precautions included food access, housing density, and access to screening and testing. Through the calls, ways to solve such challenges were addressed, with novel strategies and resources reaching the community. This medical-religious resource has proven feasible and valuable during the pandemic and warrants discussions on reproducing it for other communities during this and future infectious disease outbreaks.